TEACHER TRAINING IN COLLABORATIVE FRAMEWORKS: ADVANCES OF PARFOR AT UESPI (2021–2025) - da Cunha Santiago, Izael; Eduarda Santiago de Araujo, Maria; da Cunha Santiago, Iraneide; Pereira Campos, Edinalva; Gustavo Santiago Santos, José; Paulo Moreira dos Santos , João (Revista Gênero e Interdisciplinaridade, 2026)
This study analyzes the progress of the National Plan for the Training of Basic Education Teachers (PARFOR) at the State University of Piauí (UESPI) between 2021 and 2025, focusing on its contribution to the initial training of in-service teachers working in the public education system. The research adopts a qualitative and descriptive-analytical approach based on documentary analysis of institutional reports, public calls, administrative resolutions, pedagogical projects, and normative documents related to the program. The analysis was organized around categories such as expansion of educational offerings, institutional organization of the program, decentralization of teacher education, curricular alignment with national guidelines, and integration of educational technologies. The findings indicate that PARFOR/UESPI has expanded the offer of teacher education programs, particularly in municipalities located in the interior of the state, contributing to the reduction of regional inequalities in access to higher education. The results also show a gradual institutionalization of the program within the university through improved academic and administrative management. From a curricular perspective, the courses demonstrate alignment with the National Curriculum Guidelines and the Brazilian National Common Curricular Base while maintaining institutional pedagogical autonomy. The study concludes that PARFOR at UESPI represents a public policy in consolidation with the potential to strengthen teacher education and improve the quality of public basic education.